Rola systemów filozoficzno-religijnych w państwie i prawie japońskim po 1945 r.= The role of philosophical and religious systems in Japanese state and law after 1945 - Chodorowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author undertakes to discuss the relationship between the state and religion in Japanese law. This article aims to show the relation at the level of the state, law and religion. The latter is understood very broadly, in the context of the state in Japan, as a belief and a philosophy of life. At the same time the author looks at religion (belief) through the Japanese legislations, especially the Constitution of Japan of 11 Mars 1946, so called Showa Constitution and the existing legal regulations. Firstly, the article aims to explain the concept of religion and philosophy in Japan. Since it is difficult to clearly separate the philosophy from religion in the history of traditional Japanese thought.
Keywords: Japonia; filozofia; religia; państwo; prawo